2015
DOI: 10.1371/journal.pone.0117968
|View full text |Cite
|
Sign up to set email alerts
|

White-Matter Development is Different in Bilingual and Monolingual Children: A Longitudinal DTI Study

Abstract: Although numerous people grow up speaking more than one language, the impact of bilingualism on brain developing neuroanatomy is still poorly understood. This study aimed to determine whether the changes in the mean fractional-anisotropy (MFA) of language pathways are different between bilingual and monolingual children. Simultaneous-bilinguals, sequential-bilinguals and monolingual, male and female 10–13 years old children participated in this longitudinal study over a period of two years. We used diffusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 77 publications
(90 reference statements)
6
54
2
1
Order By: Relevance
“…In a maturation point of view, these results confirm a temporal significance for critical changes in bilinguals or those using a merging of both languages (14).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In a maturation point of view, these results confirm a temporal significance for critical changes in bilinguals or those using a merging of both languages (14).…”
supporting
confidence: 72%
“…This 141 ranges from individuals being exposed to both languages since or early after birth, and thus are actively participates in verbal-visual incongruence recognition and also in word recognition (14).…”
mentioning
confidence: 99%
“…Those who took the L2 course showed significant increases in FA in the corpus callosum over time, whereas controls did not. Similarly, Mohades et al . measured FA values for simultaneous bilinguals (L2 from birth), sequential bilinguals (L2 from age 3), and monolinguals (no L2) over a span of 2 years.…”
Section: Greater Integrity Of White Matter Structures For Bilingualsmentioning
confidence: 99%
“…To our knowledge, only two studies have compared the anatomical microstructure of bilingual and monolingual children. Mohades (Mohades et al., ; Mohades et al., ) investigated 8–11‐year‐olds and found that the white matter tract connecting anterior regions of the frontal lobe with posterior regions of the temporo‐occipital lobe in the left hemisphere (i.e., inferior occipitofrontal fasciculus, IFOF) had a higher fractional anisotropy (FA) value in simultaneous bilinguals relative to sequential bilinguals and monolinguals, suggesting that simultaneous bilingual children have more organized IFOF tracts that assist with faster processing of semantic information. Despite the dearth of studies investigating the neuroanatomy of bilingual children, findings from adult studies can suggest some initial predictions about younger populations.…”
Section: Introductionmentioning
confidence: 99%